Correlation of Alzheimer’s Disease neuropathologic staging with amyloid and tau scintigraphic imaging biomarkers - Koychev, I; Hofer, M; Friedman, N (Society for Nuclear Medicine, 2020)
PET neuroimaging of amyloid-beta (Aβ) provides an in vivo biomarker for pathologic changes associated with Alzheimer’s disease (AD). Aβ targeted agents have been approved by the FDA with additional agents, most notably targeting tau, currently under clinical investigation with one approved by the FDA in May 2020. These agents, along with non-scintigraphic biomarkers from blood and cerebrospinal fluid (CSF) have provided an opportunity to investigate the pathogenesis, prodromal changes and time course of the disease in living individuals. The current understanding of the neuropathological changes of Alzheimer’s Disease (AD) continuum is now proposed to begin up to 25 years prior to the onset of clinical symptomatology. The opportunities afforded by in-vivo biomarkers of AD, whether by CSF examination or PET, have transformed the design of AD therapeutic trials by shifting focus to the preclinical stages of disease. Future disease-modifying therapies, should they be forthcoming, will rely heavily on the use of approved biomarkers or biomarkers currently under investigation to confirm the presence of target pathology. Understanding the progressive neuropathological changes that occur in Alzheimer’s disease - and how scintigraphic findings relate to these changes - will serve the interpreting physician to fully appreciate the implications of their findings and provide a basis to interpret their examinations. The recently adopted National Institute of Ageing – Alzheimer’s Association (NIA-AA) guidelines define post mortem AD neuropathological changes as a composite score based upon three elements. These elements are the extent of involvement (spread) by cerebral Aβ based on the progression model defined by the Thal Aβ phases, the extent of involvement (spread) by neurofibrillary tangles (composed of hyperphosphorylated tau proteins) based on the progression model defined by Braak and, thirdly, the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) score, which describes the density of neuritic plaques based on certain key locations in the neocortex. This paper will review the three elements that define the NIA-AA scoring system and discuss current evidence regarding how they relate to findings based on Aβ and tau PET scintigraphy.